Diabetes attenuates urothelial modulation of detrusor contractility and spontaneous activity. (20th May 2014) - Wang, Yi; Tar, Moses T; Fu, Shibo; Melman, Arnold; Davies, Kelvin P
<x xml:space="preserve">Abstract</x> Objectives To investigate the effect of diabetes on urothelial modulation of bladder contractility. Methods Bladder strips (urothelium intact or denuded) were prepared from 8‐week‐old streptozotocin‐induced diabetic (n = 19) and non‐diabetic control rats (n = 10). The effect of modulators of MaxiK (iberiotoxin and tetraethylammonium) and Kv7 (XE991 and retigabine) potassium channel activity were investigated for their effects on both carbachol‐induced force generation and spontaneous contractile activity. Results In bladder strips from non‐diabetic animals, the presence of the urothelium resulted in marked sensitivity to carbachol‐induced force generation by modulators of MaxiK and Kv7 channel activity, whereas in the diabetic animal urothelial sensitivity to these agents was significantly diminished. Urothelial‐intact bladder strips from non‐diabetic animals were more sensitive to modulators of Kv7 activity in reducing the amplitude of spontaneous phasic contractions than urothelial‐denuded bladder strips, whereas in diabetic animals the presence or absence of the urothelium did not alter the sensitivity to modulators of Kv7 activity. Spontaneous activity in the presence of tetraethylammonium was not affected by the urothelium in bladder strips from either diabetic or non‐diabetic animals. Conclusions The presence of the urothelium in bladders from non‐diabetic animals modulates the activity of potassium blockers to affect bladder contractility, whereas in the diabetic bladder this effect is attenuated. These findings could help to explain the lack of success of pharmaceutical treatments targeting potassium channels to treat bladder pathology in patients with diseases imparing urothelial function.